1996
DOI: 10.1111/j.1600-0773.1996.tb00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Interference with Morphine Metabolism in Isolated Guinea Pig Hepatocytes

Abstract: It has previously been shown that guinea pig hepatocytes metabolise morphine in a fashion similar to humans. The metabolism of morphine (5 pM) and the formation of metabolites morphine-3-glucuronide, morphine-6-glucuronide and normorphine was studied in the absence and presence of ethanol (5, 10, 25, 60 and 100 mM) in freshly isolated guinea pig hepatocytes. In order to gain more detailed information, a mathematical model was estimated on experimental data and used to analyse the effects of ehtanol on the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…incubation further indicated that the observed effect on morphine metabolism was not mediated through inhibition of unknown pathways. This is in contr;ixf to the observed interaction between morphine and ethaiiol employing the same experimental set up, where part 01' tlic ethanol effect was due to inhibition of some unidentificd pathway (Aasmundstad et a/. 1996).…”
Section: Minutessupporting
confidence: 55%
See 2 more Smart Citations
“…incubation further indicated that the observed effect on morphine metabolism was not mediated through inhibition of unknown pathways. This is in contr;ixf to the observed interaction between morphine and ethaiiol employing the same experimental set up, where part 01' tlic ethanol effect was due to inhibition of some unidentificd pathway (Aasmundstad et a/. 1996).…”
Section: Minutessupporting
confidence: 55%
“…The reverse effect was observed whcn administering ethanol. a known cosubstrate (UDPGA) depletor (Bodd et al 1986;Aasmundstad et al 1996). The ratios between inlra-and extra-cellular concentrations of morphine, morphine-3-glucuronide and morphine-6-glucuronide were not influenced by ranitidine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation